Multicenter Phase I/II Study of Docetaxel, Cisplatin and Fluorouracil Combination Chemotherapy in Patients with Advanced or Recurrent Squamous Cell Carcinoma of the Esophagus - Yamasaki, Makoto; Miyata, Hiroshi; Tanaka, Koji; Shiraishi, Osamu; Motoori, Masaaki; Peng, Y.F.; Yasuda, Takushi; Yano, Masahiko; Shiozaki, Hitoshi; Mori, Masaki; Doki, Yuichiro (Oncology, 2011)
Objective: Esophageal squamous cell carcinoma (ESCC) is refractory to current therapeutic regimens and more effective therapies are imperative. To this end, we conducted a multicenter phase I/II trial of docetaxel, cisplatin, and fluorouracil (DCF) combination chemotherapy for ESCC. Methods: The study subjects were 46 patients with advanced or recurrent ESCC. Treatment included docetaxel at 60, 70, and 75 mg/m 2 , cisplatin at 70 mg/m 2 on day 1, and daily fluorouracil at 700 mg/m 2 on days 1 through 5. The recommended dose of docetaxel was determined in phase I, while the response rate (RR) and progression-free survival rates were analyzed in phase II. Results: The recommended dose was determined to be 70 mg/m 2 in phase I. In phase II, the RR was 72.5%. Interim analysis showed median and 1-year progression-free survival of 14 months and 55.6%, respectively. Grade 3/4 toxicities of leukopenia and neutropenia occurred in 72.5 and 90% of patients, respectively. No treatment-related death was recorded. Surgical resection was subsequently performed in 20 patients after chemotherapy, and curative resection was achieved in 19. Conclusion: DCF was tolerable and effective for advanced and recurrent ESCC. Such findings might encourage a change in the treatment strategy for ESCC.